2004
DOI: 10.1542/peds.2004-0394
|View full text |Cite
|
Sign up to set email alerts
|

Delivery Room Continuous Positive Airway Pressure/Positive End-Expiratory Pressure in Extremely Low Birth Weight Infants: A Feasibility Trial

Abstract: Objective. Although earlier studies have suggested that early continuous airway positive pressure (CPAP) may be beneficial in reducing ventilator dependence and subsequent chronic lung disease in the extremely low birth weight (ELBW) infant, the time of initiation of CPAP has varied, and there are no prospective studies of infants who have received CPAP or positive end-expiratory pressure (PEEP) from initial resuscitation in the delivery room (DR). Current practice for the ELBW infant includes early intubation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
92
2
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(102 citation statements)
references
References 23 publications
3
92
2
4
Order By: Relevance
“…21,25 Previous studies using NCPAP as a primary mode of respiratory support or following extubation reported failures requiring intubation or reintubation. [9][10][11][12][13][14][15][16]29 These investigators used different types of nasal interfaces, such as single versus binasal prongs and different CPAP generators like bubble CPAP, infant flow drivers and conventional mechanical ventilators. CPAP failure rates by 3 to 7 days ranged from 19.7 to 80% in these studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21,25 Previous studies using NCPAP as a primary mode of respiratory support or following extubation reported failures requiring intubation or reintubation. [9][10][11][12][13][14][15][16]29 These investigators used different types of nasal interfaces, such as single versus binasal prongs and different CPAP generators like bubble CPAP, infant flow drivers and conventional mechanical ventilators. CPAP failure rates by 3 to 7 days ranged from 19.7 to 80% in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…8 However, several studies have shown that a significant number of infants treated with NCPAP alone or following extubation from MVET fail NCPAP and require reintubation. [9][10][11][12][13][14][15] Furthermore, two recent large trials 11,15 evaluating the effects of early NCPAP did not show a decrease in BPD. The most common reasons for extubation failure are recurrent apnea, bradycardia or desaturations, and or development of respiratory acidosis.…”
Section: Introductionmentioning
confidence: 99%
“…More recent clinical trials in other pediatric populations support this variation with rates ranging from 52% to 89%. [5][6][7][8][9] Within the RESTORE clinical trial consent rates varied per arm; 69% to 97% in the control arm, where consent was obtained for data collection only and 41% to 90% in the intervention arm, where parents were asked for permission to allow management of their child's sedation per the RESTORE protocol. Parent consent rates affect the total duration of pediatric clinical trials.…”
Section: Asking For Parental Permissionmentioning
confidence: 99%
“…In a multicenter, randomized study, 80% of ELBW infants required intubation by 7 days of age. 30 34 showed that bubbling rates during bubble CPAP had no effect on ventilation or oxygenation. In preterm lambs, lung volumes were higher with bubble CPAP as compared to conventional CPAP.…”
Section: Noninvasive Ventilation Strategiesmentioning
confidence: 99%